Training and influence of maximal strength in football players. With specific emphasis on females - Pedersen, S. (2021)
The aims of the thesis were to study association between strength (1 repetition maximum (1RM) half-squat strength), 5-, 10- and 15 m sprint, countermovement jump (CMJ)), and physical match play performance in high level female football players. Further, the next aim was to investigate whether maximal strength training result in improvements in strength, and whether it associated with improvements in sprint and jump height performance, as well as physical match play performance in female football players. Next, we investigated whether previous findings reported following MST for male players reproduced in our lab in paper III, as well as how those these findings compare with findings in female players from paper II. Finally, an aim was to study the effect of a prescribed unsupervised 12-week home- and group-based training program without gym facilities, for 1RM half-squat strength, CMJ, and 5 m, 10 m, and 15 m sprint time in female high-level football players during a period without full contact football training. Our findings indicate maximal strength is of minor importance for physical match play performance, and far lower than other test variables, such as CMJ and sprint times, which were associated with physical match play performance. MST is feasible and effective for increasing maximal strength in female football players, however the importance of MST for sprint and jump performance in female football players was minimal. We found a limited impact of exercise including MST, on sprint times = 15 m, and jump height. When male players of the same relative strength level at baseline carried out MST, an improvement in sprint and jump performance was found. Further, excluding systematical MST and restricting access to training gyms over a period of COVID-19 lockdown, with the prescription of only body weight exercises and without maximal strength training, did not negatively influence maximal strength, sprint times or jump height in female high-level football players. This has implications for periods without access to football- or strength training facilities.